PENERAPAN MEDIA GEOGEBRA PADA PEMBELAJARAN MATEMATIKA - Sri Wahyuni; Naning Sutriningsih; Siti Rahayu (Program Studi Pendidikan Matematika FIP UNHASY, 2023)
This study aims to determine (1) if there are the differences of students’ outcomes between students who use GeoGebra learning media and those who do not use GeoGebra learning media; and (2) which learning outcome is better between students wwho use GeoGebra learning media and those who do not use GeoGebra learning media. This research is quantitative research. The population of this study were all XI IIS students with the sample of the study being 60 students of XI IIS 2 and XI IIS 3 which were selected using clustrer random sampling. Data was collected by using a test instrument anda analyzed by using the t-test previously carried out the normality and the homogeneity test. The result of this study were: (1) there are differences of students’ outcomes between students who use GeoGebra learning media and those who do not use GeoGebra learning media and (2) the learning outcome of students who use GeoGebra learning media was better than students who do not use GeoGebra learning media.